2018
DOI: 10.1038/s41598-018-35698-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing the mosaic genome of Brahman cattle identifies historic and recent introgression including polled

Abstract: Brahman cattle have a Bos indicus and Bos taurus mosaic genome, as a result of the process used to create the breed (repeat backcrossing of Bos taurus females to Bos indicus bulls). With the aim of identifying Bos taurus segments in the Brahman genome at sequence level resolution, we sequenced the genomes of 46 influential Brahman bulls. Using 36 million variants identified in the sequences, we searched for regions close to fixation for Bos indicus or Bos taurus segments that were longer than expected by chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 56 publications
2
54
0
1
Order By: Relevance
“…In the USA, the import of zebu led to the development of the popular transboundary Brahman zebu breed, which has taurine mtDNA as well as an autosomal taurine ancestry of 9% (Koufariotis et al . 2018). Zavarez et al .…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%
“…In the USA, the import of zebu led to the development of the popular transboundary Brahman zebu breed, which has taurine mtDNA as well as an autosomal taurine ancestry of 9% (Koufariotis et al . 2018). Zavarez et al .…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%
“…A genome-wide alignment of DNA fragments from a B. taurus individual differs from the Herefordbased reference sequence at between 7 and 8 million single nucleotide polymorphisms (SNPs) and small (<50 bp) insertions and deletions (Indels) [12,13]. The number of differences is higher for DNA samples with greater divergence from the reference [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Here we demonstrate a new approach that yielded haplotype-resolved Brahman and Angus cattle genomes from an F1 hybrid of the two subspecies. Our analyses demonstrated that previous studies which mapped indicine sequences onto the taurine reference UMD3.1.1 4,11 likely inflated the number of genetic variants that are present between the two subspecies by up to 4%.…”
Section: Discussionmentioning
confidence: 58%
“…Here we demonstrate a new approach that yielded highly contiguous, haplotype-resolved Brahman and Angus cattle genomes from an F1 hybrid of the two subspecies. Our analyses demonstrated that previous studies which mapped indicine sequences onto the taurine reference UMD3.1.1 4,11 likely inflated the number of genetic variants that are present between the two subspecies by up to 4%. Calling SNPs in transcripts from a diploid hybrid with both haplo-genomes decoded provides accurately phased transcripts for studies on the role of allele-specific expression in, e.g., hybrid vigor or heterosis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation